POTENTIAL REVENUE OF VALUE ADDED TAX FROM TRADE TRANSACTIONS THROUGH THE ELECTRONIC SYSTEM - Agrevinna Beatrice; Sri Yani Kusumastuti (Institut Teknologi dan Ilmu Sosial Khatulistiwa, 2023)
This study aims to estimate the potential revenue of taxing the digital commerce transaction in Indonesia by implementing Value Added Tax on e-Commerce. The estimation is calculated from Indonesia’s electronic commerce projection from Statista in three scenarios, optimistic scenario, moderate scenario, and pessimistic scenario. The estimated VAT on e-Commerce revenues from these three scenarios are then compared with the VAT revenue in State Budget 2020. The estimations show that imposing VAT on e-commerce can raise 3,02-5,35% VAT revenue target in 2020.